La professionnalisation des enseignants de langues étrangères vietnamiens : entre tradition et industrialisation. Etude comparative entre enseignants des secteurs public et privé - Nguyễn, Đỗ Thiên Vũ (Caen Normandie Université, 2020)
During recent years, education and training have experienced greater phenomena of industrialization in particular under the influence of the development of technologies. The field of foreign language teaching and learning (FLT) has also undergone changes due to the internationalization of certification standards and the growth of private training sector. The foreign language teaching field in Vietnam is not immune to these developments that inevitably lead to significant changes in the process of professionalization of the teaching staff. Our research aims at highlighting the way foreign language teachers in both public and private sectors represent their professionality in this new context and the priorities they consider important in terms of professionalization. To do this, we conducted our empirical research in two stages : a pre-survey by interviews with colleagues in Dalat and a supplementary survey by an online questionnaire. The analysis of the 14 semi-structured interviews of the first phase helped us to build the questionnaire that was intended for a wider audience of teachers in the country. Our questionnaire survey (N 364) allowed us to draw three different profiles which are differently positioned in terms of the evolution of FLT. The discussion of the determinants of each profile provides a better understanding of the professional development dynamics of Vietnamese foreign language teachers.